Repurposing vitamin D for treatment of human malignancies via targeting tumor microenvironment - Xu Wu; Wei Hu; Lan Lu; Yueshui Zhao; Yejiang Zhou; Zhangang Xiao; Lin Zhang; Hanyu Zhang; Xiaobing Li; Wanping Li; Shengpeng Wang; Chi Hin Cho; et al. (Elsevier, 2019)
Tumor cells along with a small proportion of cancer stem cells exist in a stromal microenvironment consisting of vasculature, cancer-associated fibroblasts, immune cells and extracellular components. Recent epidemiological and clinical studies strongly support that vitamin D supplementation is associated with reduced cancer risk and favorable prognosis. Experimental results suggest that vitamin D not only suppresses cancer cells, but also regulates tumor microenvironment to facilitate tumor repression. In this review, we have outlined the current knowledge on epidemiological studies and clinical trials of vitamin D. Notably, we summarized and discussed the anticancer action of vitamin D in cancer cells, cancer stem cells and stroma cells in tumor microenvironment, providing a better understanding of the role of vitamin D in cancer. We presently re-propose vitamin D to be a novel and economical anticancer agent. KEY WORDS: Vitamin D, 1α,25-Dihydroxyvitamin D3, Tumor microenvironment, Cancer stem cell, Tumor-infiltrating lymphocyte, Tumor-derived endothelial cell, Cancer-associated fibroblast